Numerical analysis of the Cargo Transfer Vessel offloading operation in a Brazilian oil field. (1st February 2021) - Tannuri, Eduardo A.; Huang, Alex S.; Queiroz Filho, Asdrubal N.; Ferreira, Marcos D.; Passarelli, Fábio M.; Korneliussen, Pål B.; Stuberg, Petter
Abstract: In a new concept of offloading operation, the oil from a spread moored FPSO is transferred to a conventional Tanker with an intermediate Cargo Transfer Vessel (CTV) equipped with a DP system. A comprehensive numerical analysis of the CTV offloading operation is here developed considering the sea states in the Libra Field, Brazil. First, the environmental loads on the vessels were estimated. Current and wind forces coefficients were obtained using the CFD software StarCCM+, while wave coefficients were obtained using WAMIT. For the 10-year metocean data, the multi-body static equilibrium configurations of the system – composed of the CTV, Conventional Tanker and Tugboat - were calculated. With those results, it was possible to estimate the downtime considering different offloading sectors and to compare with the DP Shuttle Tanker operation. Finally, a 5-day campaign of real-time simulations was carried out with the presence of DP Operators and captains, to verify critical conditions, considering the human factor. Each vessel was simulated in an individual cabin. For the simulations, the real DP System was integrated with the numerical simulator in a Hardware-in-the-loop configuration, resulting in a more realistic simulation. Highlights: Fast and real-time simulators are used to estimate the uptime of a complex multi-body offloading operation. The real DP System is integrated with the simulator in a hardware-in-the-loop architecture, better representing the reality. Extra terms in the DP logic eliminate the longitudinal motion instability of a large tanker coupled to the DP vessel.